Il benessere come bene comune. Una forte coscienza filosofica e un fondato impegno pedagogico - Falaschi, Elena (Studi sulla Formazione/Open Journal of Education, 2017)
The well-being is constituted today as a common good to be protected and to be supported, in all contexts and in all stages of life. The reference to the philosophical conscience, to the pedagogical engagement and to the political responsibility are an valid and effective “integrated system” to ensure to all the internalization of meanings, the opportunity of aware choices, the investment in future projects in the direction of well-being.